Heart Rate and Heart Rate Variability Changes Are Not Related to Future Cardiovascular Disease and Death in People With and Without Dysglycemia: A Downfall of Risk Markers? The Whitehall II Cohort Study - Hansen, Christian S; Jørgensen, Marit E; Malik, Marek; Witte, Daniel R; Brunner, Eric J; Tabák, Adam G; Kivimäki, Mika; Vistisen, Dorte (Diabetes care, 2021)
OBJECTIVE: Higher resting heart rate (rHR) and lower heart rate variability (HRV) are associated with increased risk of cardiovascular disease (CVD) and all-cause mortality in people with and without diabetes. It is unknown whether temporal changes in rHR and HRV may contribute to this risk. We investigated associations between 5-year changes in rHR and HRV and risk of future CVD and death, taking into account participants' baseline glycemic state. RESEARCH DESIGN AND METHODS: In this prospective, population-based cohort study we investigated 4,611 CVD-free civil servants (mean [SD] age, 60 [5.9] years; 70% men). We measured rHR and/or six indices of HRV. Associations of 5-year change in 5-min rHR and HRV with fatal and nonfatal CVD and all-cause mortality or the composite of the two were assessed, with adjustments made for relevant confounders. Effect modification by glycemic state was tested. RESULTS: At baseline, 63% of participants were normoglycemic, 29% had prediabetes, and 8% had diabetes. During a median (interquartile range) follow-up of 11.9 (11.4; 12.3) years, 298 participants (6.5%) experienced a CVD event and 279 (6.1%) died of non-CVD-related causes. We found no association between 5-year changes in rHR and HRV and future events. Only baseline rHR was associated with all-cause mortality. A 10 bpm-higher baseline HR level was associated with an 11.4% higher rate of all-cause mortality (95% CI 1.0-22.9%; P = 0.032). Glycemic state did not modify associations. CONCLUSIONS: Changes in rHR and HRV and possibly also baseline values of these measures are not associated with future CVD or death in people with or without dysglycemia.
Keywords: diabetes mellitus; Cohort Studies; Middle Aged; Diabetes Mellitus; mužské pohlaví; Prospective Studies; Heart Rate; kohortové studie; srdeční frekvence; Cardiovascular Diseases; ženské pohlaví; Humans; prospektivní studie; lidé středního věku; rizikové faktory; Female; Risk Factors; kardiovaskulární nemoci; lidé; Male